2020
DOI: 10.1111/scs.12869
|View full text |Cite
|
Sign up to set email alerts
|

Being a volunteer encountering older people’s loneliness and existential loneliness: alleviating loneliness for others and oneself

Abstract: Background The increasing proportion of older people worldwide is challenging society and the healthcare sector to develop new solutions, such as involving volunteers, especially to combat loneliness among older people. Loneliness is a broad concept comprising, for example existential loneliness – a deep feeling of aloneness in the world. We know little about volunteers’ experience of encountering older people’s loneliness in general and existential loneliness in particular. Such knowledge is important in orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…A total of 20 the 155 included studies conceptualised existential loneliness [159][160][161][162][163][164][165][166][167][168][169][170][171][172][173][174][175][176][177][178]. In contrast to emotional or social loneliness, existential loneliness was defined as a feeling of fundamental separateness from others and the wider world, not simply as the absence of meaningful relationships and negative emotional experience.…”
Section: Existential Lonelinessmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 20 the 155 included studies conceptualised existential loneliness [159][160][161][162][163][164][165][166][167][168][169][170][171][172][173][174][175][176][177][178]. In contrast to emotional or social loneliness, existential loneliness was defined as a feeling of fundamental separateness from others and the wider world, not simply as the absence of meaningful relationships and negative emotional experience.…”
Section: Existential Lonelinessmentioning
confidence: 99%
“…In contrast to emotional or social loneliness, existential loneliness was defined as a feeling of fundamental separateness from others and the wider world, not simply as the absence of meaningful relationships and negative emotional experience. Participants described it as a feeling that occurred when important others were absent through some form of psychological rejection or absence [159,161,162], or when people felt left behind by life events, such as death or divorce, and/or experiences of physical or mental decline or limitation through illness, traumatic experience, aging, and a sense of one's mortality [160,[163][164][165][166][167][168][169][170][171][172][173][174][176][177][178]. Similar explanations of existential loneliness were reported by healthcare professionals supporting older people experiencing this type of loneliness [175].…”
Section: Existential Lonelinessmentioning
confidence: 99%
“…However, existential loneliness may be difficult to recognize, since it is not always obvious. In previous studies it has been shown that nursing staff and volunteers found it challenging to recognize and meet older people’s existential loneliness (Sundström et al, 2021 , 2018 ). In addition, health care professionals found it challenging to deal with young adults’ existential concerns, and they needed support to create an inviting atmosphere and stay present, since the conversations could stir up their own existential issues (Lundvall et al, 2019b ).…”
Section: Discussionmentioning
confidence: 99%
“…In other research, it is taken as a state in which one needs social contact but does not have the means to acquire it [35]. Meanwhile, some definitions of loneliness claim it as something that "can be measured objectively in terms of the number of friends and social contacts" [36], while others define it as a subjective feeling that occurs when social relationships are deficient in some way [4] quantitatively or qualitatively [37]. Mansfield et al [38] have provided a review of these definitions and concluded that while these concepts of SI and loneliness are distinct concepts, there are many definitions in use that make them often interchangeable, and their phenomena have complex interactions in the human experience.…”
Section: Discussionmentioning
confidence: 99%